The specific of the genre of V. Levental’s novel “Mary Regina” - A D Magliy (RUDN Journal of Studies in Literature and Journalism, 2015)
The article is devoted to the analysis of genre features of the novel “Mary Regina” of St. Petersburg writer V. Levental. The main theme of creativity, the profession of the protagonist - a film director and also the presence of salient genre features (the motifs of creation, the conflict: the сreator and the world) allow to define the genre of this novel as “a novel about the artist”. Levental draws a parallel between the physical processes occurring in space and on Еarth, shows their community and similarity: the life of the heroine Masha Regina, has grown from a provincial girl to film director - world-renowded star, is shown by the author in comparison with the laws of the development of stars: their birth, evolution and death. The structure and the composition of the novel are based on the model of a “Cross cap”, which symbolizes the infinity of the universe that can relate it to such genre modification, as “a novel-model of the world”.